Optimalisasi Penerapan Kegiatan Literasi dalam Meningkatkan Minat Baca Siswa Sekolah Dasar - Nadia Fitriani; Adrias Adrias; Aissy Putri Zulkarnaini (Politeknik Kampar, 2025)
This study aims to provide an overview of efforts to optimize literacy activities in increasing students' interest in reading, especially at the elementary school level. This study uses a descriptive qualitative approach with elementary school students as the research subjects. Data collection techniques are carried out through literature reviews of scientific sources, such as books, academic journals, and proceedings from various scientific seminars both at national and international levels. The data obtained are analyzed using descriptive analysis methods, with an emphasis on describing the phenomena that occur and a solution-oriented approach to the problem of low student interest in reading. Based on the results of the study, it was found that structured and enjoyable reading activities need to be continuously encouraged and developed. In fact, these activities should not only be routine, but also become part of a learning culture that is inherent in students' daily lives. Thus, efforts to increase literacy are very important in shaping the future of a bright young generation. Instilling awareness of the importance of reading must be done early on, especially in elementary school environments, so that interest in reading can grow naturally. In addition, support is needed from all parties, including teachers, parents, and other educational institutions, to create a learning environment that supports the development of literacy. By getting used to reading and utilizing knowledge from various reading sources, students can enrich their insights and improve the quality of their thinking in everyday life.